CO2 laser drilling coupled with moderate electric fields for enhancement of the mass transfer phenomenon in a tomato (Lycopersicon esculentum) peeling process. (July 2020) - Silva-Vera, Wladimir; Avendaño-Muñoz, Natalia; Nuñez, Helena; Ramírez, Cristian; Almonacid, Sergio; Simpson, Ricardo
Abstract: Tomatoes are listed as the most consumed vegetables around the world, with a profitable market into the peeled-canned tomato industry. In this sense, the lye method is commonly performed as peeling method, but with severe impact on the environment. Therefore, this study focuses on modifying the surface of tomato skin by using laser CO2 drilling under different pore size (127.92–194.39 μm), pore density (2–9 pore·cm −2 ) and coupled with moderate electric field (MEF) at 1333 V m −1 to facilitate its removal. The variables NaOH concentration, pore density and pore size were tested. As a result, the effective diffusion coefficient for the drilled skin ranged between 4.45 × 10 −11 and 24.95 × 10 −11 m 2 s −1 at 60 °C (p-value < 0.05). Likewise, a decrease in total work, peak load and Young's modulus was noticeable compared to conventional treatment (p-value < 0.05). Therefore, the laser CO2 drilling might improve the skin removal with less energy and lower NaOH concentration compared to conventional treatment. Highlights: CO2 Laser drilling on the tomato skin improved the lye peeling diffusion. Facilitated remotion of tomato skin drilled is expected after treatment. Saving in NaOH quantity is achieved using drilling as pre-treatment. Longer laser pulse time seems to increase the crust formation around pores. Combustion during laser ablation was subject to thermal properties of solid.